Interdisciplinary Approach in Treatment of Endodontic- Periodontal Lesion : A Case Report - Somanath, G; George, G; Sinha, JN; Gautam, V (Journal of Universal College of Medical Sciences, 2013)
Endodontic periodontal combined lesion is a clinical dilemma because making a clinical diagnosis and deciding a prognosis are difficult. The treatment of endodontic periodontal lesion combined requires both endodontic therapy and periodontal regenerative procedures. This case report evaluates the prognosis of endo- perio lesion which was first treated with conventional endodontic therapy and then followed by periodontal therapy. At a three month post operative evaluation there was gain of clinical attachment level and reduction in probing depth with radiographic evidence of substantial alveolar bone gain. DOI: http://dx.doi.org/10.3126/jucms.v1i3.8768 Journal of Universal College of Medical Sciences Vol.1(3) 2013: 58-61